Systematic Literature Review: Efektivitas Komunikasi Organisasi Internal Terhadap Kinerja Karyawan - Dea Wisnu Ramdani; Indy Fauziah Hanifa; Lailafitri Pratiwi Kadmadi; Aisyah Humayyrah; Sofa Perihah Nurasiah (Jurnal Ilmu Sosial dan Humaniora, 2026)
Internal organizational communication is a crucial factor in improving employee performance through information delivery, work coordination, and the establishment of effective relationships within the organization. However, previous research findings regarding the influence of internal communication on employee performance differ, necessitating a more comprehensive study. This study aims to analyze the effectiveness of internal organizational communication on employee performance through a Systematic Literature Review (SLR) approach. The study was conducted by identifying, selecting, evaluating, and synthesizing scientific articles published between 2020 and 2026. The literature search was conducted using Google Scholar through the Publish or Perish application, using the keywords organizational internal communication, employee performance, organizational communication effectiveness, and internal communication. The results indicate that most studies conclude that internal organizational communication has a positive and significant effect on employee performance. Communication effectiveness is influenced by factors such as teamwork, work motivation, work discipline, work environment, job descriptions, employee empowerment, rewards and punishments, and the use of digital communication media. Conversely, ineffective communication can lead to miscommunication, poor coordination, and decreased productivity. Therefore, organizations need to build open, transparent internal communication supported by digital technology to improve communication effectiveness and optimize employee performance.